Transcriptome and functional analysis revealed the intervention of brassinosteroid in regulation of cold induced early flowering in tobacco - Dai, Xiumei; Zhang, Yan; Xu, Xiaohong; Ran, Mao; Zhang, Jiankui; Deng, Kexuan; Ji, Guangxin; Xiao, Lizeng; Zhou, Xue (Frontiers in Plant Science, 2023)
Cold environmental conditions may often lead to the early flowering of plants, and the mechanism by cold-induced flowering remains poorly understood. Microscopy analysis in this study demonstrated that cold conditioning led to early flower bud differentiation in two tobacco strains and an Agilent Tobacco Gene Expression microarray was adapted for transcriptomic analysis on the stem tips of cold treated tobacco to gain insight into the molecular process underlying flowering in tobacco. The transcriptomic analysis showed that cold treatment of two flue cured tobacco varieties (Xingyan 1 and YunYan 85) yielded 4176 and 5773 genes that were differentially expressed, respectively, with 2623 being commonly detected. Functional distribution revealed that the differentially expressed genes (DEGs) were mainly enriched in protein metabolism, RNA, stress, transport, and secondary metabolism. Genes involved in secondary metabolism, cell wall, and redox were nearly all up-regulated in response to the cold conditioning. Further analysis demonstrated that the central genes related to brassinosteroid biosynthetic pathway, circadian metabolism, and flowering pathway were significantly enhanced in the cold treated tobacco. Phytochemical measurement and qRT-PCR revealed an increased accumulation of BL and a decreased expression of the flowering locus c gene. Furthermore, we found that overexpression of NtBIR1 could induce early flowering in tobacco under normal condition. And low-temperature-induced early flowering in NtBIR1 overexpression plants were similar to that of normal condition. Consistently, low-temperature-induced early flowering is partially suppressed in NtBIR1 mutant. Together, the results suggest that cold could induce early flowering of tobacco by activating BR signaling.